Children's Enjoyment, Perceived Competency, and Vigorous Physical Activity During High-Intensity Interval Training in Physical Education. Issue 4 (2nd October 2022) - Burford, Katie; Gillespie, Kathryn; Jowers, Esbelle M.; Bartholomew, John B.
ABSTRACT: Purpose : Little is known about children's experience with high-intensity interval training (HIIT) during elementary school. Perceptions of enjoyment, perceived competence, and motivation are likely to drive long-term adherence and are, therefore, critical to understanding how HIIT might be implemented in this setting. The purpose of this study was to describe children's vigorous physical activity (VPA), enjoyment, and perceived competency of HIIT activities within a Self-Determination Theory framework (autonomy) in elementary school physical education (PE) classes. Methods : Participants were 402 children from a single, diverse elementary school (49.4% female, 59.6% Non-Hispanic white). Student enjoyment and perceived competency were collected following teacher- (non-autonomous) and student-led (autonomous) conditions. A sub-set of 201 children wore accelerometers to measure percent of time in VPA during HIIT conditions. This mixed factorial design was assessed through a series of repeated measures ANOVAs. Results : While children reported generally positive enjoyment and perceived competence in both conditions (rating over 4.0 on a 5-point scale), children significantly enjoyed (d = 0.44) and felt more competent ( d = 0.11) during the autonomous HIIT condition compared to the nonautonomous HIIT condition. In contrast, the percent of time in VPA ( d = 0.94) was significantly lower in the autonomous condition. Conclusions : These data illustrate a challenging trade-off with the design of HIIT trials. Increasing autonomy through the inclusion of student choice increased enjoyment and perceived competence of HIIT, which are likely to improve adherence, but lowered VPA, which is likely to reduce cardiometabolic impact.Abbreviations : U.S.: United States; PA: Physical activity; MVPA; Moderate-to-vigorous physical activity; PE: Physical education; CDC: Centers for Disease Control and Prevention; Randomized control trial, RCT; SDT: Self-Determination Theory; HIIT: High-intensity interval training; RCT: Randomized control trial; VPA: Vigorous physical activity; IRB; Institutional Review Board; HFZ: Healthy Fitness Zone; PACES: Physical Activity Enjoyment Scale; M: Mean; SD: Standard deviation